2023
DOI: 10.1002/hed.27289
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of perioperative vasopressor use for hemodynamic management of patients undergoing free flap surgery: A systematic review and meta‐analysis

Abstract: This systematic review and meta‐analysis investigates the objective evidence regarding outcomes in head and neck free flap surgeries using vasoactive agents in the perioperative period. A search was performed in PubMed, Cochrane, Web of Science, and Scopus databases. Inclusion criteria were clinical studies in which vasopressors were used in head and neck free flap surgery during the intraoperative and perioperative period. Eighteen studies (n = 5397) were included in the qualitative analysis and nine (n = 438… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The two groups before (n = 346) versus monitored (GDHT) (n = 68) had no statistically significant differences in terms of age, comorbidities (Charlson score), past medical history of hypertension, and duration of anesthesia (Table 1). When comparing the two groups before versus monitored, the number of episodes of IOH and the total duration of IOH did not significantly change with the use of hemodynamic monitoring (respectively, 6 [2][3][4][5][6][7][8][9][10][11][12] vs. 8 [3][4][5][6][7][8][9][10][11][12][13][14] p = 0.15; and 93 vs. 109 [47-180] min, p = 0.21).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The two groups before (n = 346) versus monitored (GDHT) (n = 68) had no statistically significant differences in terms of age, comorbidities (Charlson score), past medical history of hypertension, and duration of anesthesia (Table 1). When comparing the two groups before versus monitored, the number of episodes of IOH and the total duration of IOH did not significantly change with the use of hemodynamic monitoring (respectively, 6 [2][3][4][5][6][7][8][9][10][11][12] vs. 8 [3][4][5][6][7][8][9][10][11][12][13][14] p = 0.15; and 93 vs. 109 [47-180] min, p = 0.21).…”
Section: Resultsmentioning
confidence: 94%
“…7 The avoidance of IOH due to vasodilation is even more challenging in free flap cases as the use of vasopressors to maintain blood pressure is still a matter of debate even if recent studies have reported that it does not increase the risk of flap complications. 8,9 In these conditions, avoiding fluid administration or vasopressors may expose FTT patients to long periods of IOH, especially during times of minimal stimulation (e.g., microvascular anastomosis) leading to flap and organ hypoperfusion and dysfunction. 4,6 Several surgical specialties (e.g., major abdominal surgery) have made extensive use of goal-directed hemodynamic therapy (GDHT) based on relatively noninvasive cardiac output (CO) monitoring to optimize fluid balance during and after surgery, which has resulted in a decrease in postoperative morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the TSA on major medical complications showed a Z-line between the two conventional boundaries, with a ratio of patients recruited/needed of n = 417/4805 (Figure 4), therefore suggesting the need for further research on this outcome. The promising results regarding the use of vasopressors in free flap surgery, as demonstrated by Michelle et al, 1 appear robust and may not require further validation. However, additional studies are warranted to explore the impact of vasopressors on major clinical complications in this type of surgery.…”
mentioning
confidence: 89%
“…We commend Michelle et al for their work suggesting that intraoperative vasopressor use does not negatively impact free tissue transfer outcomes in head and neck surgery. 1 Michelle et al found managing intraoperative hypotension during free flap surgery did not appear to increase the risk of complete or partial necrosis of the flap necessitating removal or replacement. Furthermore, the use of vasopressors reduced the odds ratio of total complications (OR = 0.65, 95% CI [0.52, 0.82], p < 0.001) and flap complications (OR = 0.69, 95% CI [0.55, 0.87], p = 0.002), indicating a potential beneficial role.…”
mentioning
confidence: 99%